Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/ece3.10419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape structure and patch characteristics on the density of central populations of the eastern green lizard Lacerta viridis

Ana María Prieto‐Ramírez

Abstract: A better understanding of the impact of habitat loss on population density can be achieved by evaluating effects of both parameters within remnant habitat patches and parameters of the landscape surrounding those patches. The integration of predictors at the patch and landscape level is scarce in animal ecological studies, especially for reptiles. In this study, a patch–landscape approach was applied to evaluate the combined effects of within‐patch habitat quality, patch geometry and landscape configuration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…Contrary to our prediction and the results of some previous studies (Doherty et al 2020;Prieto-Ramírez 2023;Woolley et al 2023), we found that urban land use cover was positively correlated with the mean abundance of snakes (Fig. 2A; Table 5), implying that populations living in more urbanized habitats are more abundant.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our prediction and the results of some previous studies (Doherty et al 2020;Prieto-Ramírez 2023;Woolley et al 2023), we found that urban land use cover was positively correlated with the mean abundance of snakes (Fig. 2A; Table 5), implying that populations living in more urbanized habitats are more abundant.…”
Section: Discussioncontrasting
confidence: 99%
“…Importante acción de deterioro cumple los micro plásticos en los esquemas de agua dulce, aunque no es un indicador de la calidad ecológica tienen efectos nocivos que deben ser estudiados, se observaron altos niveles de nutrientes principalmente el fósforo, el intestino de oligoqueto presentó alto número de micro plásticos a la vez desnutrición y trastornos digestivos (Cheng et al, 2023;Prieto-Ramírez, 2023;Ribeiro et al, 2023).…”
Section: Los Microplásticosunclassified